Enhancing the performance of elite speed skaters using SkateView: A new device to measure performance in speed skating - van der Eb, J.; Gereats, S.; Knobbe, A. (Proceedings, 2020)
In speed skating, environmental circumstances and the near-frictionless movement of the skate in a fore-aft direction over the ice make it difficult to measure technical performance parameters on a regular basis while training in an indoor speed skating rink. SkateView has been developed to overcome these challenges, comprising of two IMU`s (Inertial Measurement Unit), ultra-light force sensors, a mobile phone and an app providing feedback to coach and skater. The feedback, directly on the ice or shortly after a training session, consists of basic parameters like ice contact time, stroke frequency and lap times, and more parameters can be added. Stroke frequency is an important performance parameter, which is presented on a stroke-by-stroke basis and provides a direct insight into the activity.